The road to good spirits: perceived stress, self esteem and coping skills in patients with alcohol dependence - Ghorpade, Geetanjali S.; Kadam, Kranti S.; Angane, Amey Y.; Unnithan, Vishnu B. (International Journal of Research in Medical Sciences, 2020)
Background: Alcohol is the commonest psychoactive substance used by Indians. Stress and self-esteem issues may cause alcohol use as a coping mechanism. The purpose of this study was to analyze the severity of alcohol dependence, gauge levels of perceived stress and self-esteem and study coping skills in patients. It further examined the relations between sociodemographic variables of patients, their perceived stress, self esteem and coping skills as well as duration and severity of alcohol dependence. Methods: Cross-sectional study of 200 patients with alcohol use disorder recruited by complete enumeration technique was undertaken. They were administered a semi-structured questionnaire along with Perceived Stress Scale (PSS-10), Rosenberg’s Self-Esteem Scale (RSES), Coping Inventory for Stressful situations (CISS-21) and Severity of Alcohol Dependence Questionnaire (SADQ). Associations and correlations were examined. Results: Almost half the patients had severe alcohol dependence. Less than one-fourth of the patients had low self esteem. There was a significant negative correlation between self esteem and severity of alcohol dependence as well as duration of alcohol use. Nearly half the patients had high perceived stress. There was a significant positive correlation between severity of alcohol dependence and perceived stress. Majority patients used task oriented coping skills. Patients of alcohol dependence having low self-esteem used predominantly avoidant-oriented coping skills. Conclusions: This study highlights the importance of thorough evaluation and screening in patients having alcohol dependence for self-esteem issues and perceived stress levels. Teaching effective coping skills, supportive psychotherapy and counselling can be effective. Multimodal treatment protocols will effectively lighten the stress caused by alcohol dependence.